Analisis Sistem Informasi Akuntansi Penerimaan Dan Pengeluaran Barang Pada PT. Dua Samudra Logistik Palembang - Rahmadani, Novi; Noviardy, Andrian; Sartika, Dewi; Terzaghi, M. Titan (Jurnal Ekonomika Dan Bisnis (JEBS), 2024)
The purpose of this research is to see and study the accounting information system, which is a process that is influenced by the admin, warehouse department, finance department, and other departments. This system is designed to provide sufficient assurance to achieve objectives related to receiving, issuing, and shipping goods. This research uses a qualitative descriptive approach and uses primary and secondary data. Data collection is done through interviews, observation, and documentation. The results of this study indicate that recording inventory using the permanent method is good enough for the accounting information system for receiving and issuing goods. PT Dua Samudra Logistik Palembang uses the FIFO method to value inventory. The earliest incoming goods with the longest DO date are the earliest shipped. This study focuses on the Accounting Information System for Receipt and Expenditure of Goods at PT. Dua Samudra Logistik Palembang.